An Update Review on the Anthelmintic Activity of Bitter Gourd, Momordica charantia - Poolperm, Sutthaya; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Momordica charantia (Family: Cucurbitales), as known as bitter melon or gourd, is a daily consumption as food and traditional medicinal plant in Southeast Asia and Indo‑China. It has been shown to possess anticancer, antidepressant, antidiabetic, anti‑inflammatory, antimicrobial, antiobesity, antioxidant, and antiulcer properties. Its common phytochemical components include alkaloids, charantin, flavonoids, glycosides, phenolics, tannins, and terpenoids. This plant is rich in various saponins including momordicin, momordin, momordicoside, karavilagenin, karaviloside, and kuguacin, all of which have been reported to contribute to its remedial properties including antibacterial, antifungal, antiviral, and antiparasitic infections. Based on established literature on the anthelmintic activity of M. charantia and possible mode of action, this review article has attempted to compile M. charantia could be further explored for the development of potential anthelmintic drug.
Keywords: Helminth; infection; Momordica charantia; plant; traditional medicine; worm